2013
DOI: 10.1186/1471-2164-14-859
|View full text |Cite
|
Sign up to set email alerts
|

Repertoire, unified nomenclature and evolution of the Type III effector gene set in the Ralstonia solanacearum species complex

Abstract: BackgroundRalstonia solanacearum is a soil-borne beta-proteobacterium that causes bacterial wilt disease in many food crops and is a major problem for agriculture in intertropical regions. R. solanacearum is a heterogeneous species, both phenotypically and genetically, and is considered as a species complex. Pathogenicity of R. solanacearum relies on the Type III secretion system that injects Type III effector (T3E) proteins into plant cells. T3E collectively perturb host cell processes and modulate plant immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
287
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 204 publications
(295 citation statements)
references
References 69 publications
(147 reference statements)
7
287
0
1
Order By: Relevance
“…This hypothesis is in accordance with a polymutant approach in Pst DC3000 which highlighted a consortium of redundant translocators required to promote Pst T3E injection into plant cells (61,62). RipF1, RipW, RipX, RipAB, and RipAM all belong to the R. solanacearum core effectome (11). It will be of particular interest to study more precisely how they take part in the formation of the Hrp translocation apparatus as acces- sory cotranslocators, notably by looking for interactions between them and the HrpY pilin.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…This hypothesis is in accordance with a polymutant approach in Pst DC3000 which highlighted a consortium of redundant translocators required to promote Pst T3E injection into plant cells (61,62). RipF1, RipW, RipX, RipAB, and RipAM all belong to the R. solanacearum core effectome (11). It will be of particular interest to study more precisely how they take part in the formation of the Hrp translocation apparatus as acces- sory cotranslocators, notably by looking for interactions between them and the HrpY pilin.…”
Section: Discussionsupporting
confidence: 83%
“…3B). These experiments showed that RSp0213 encodes a T3E, which was therefore renamed RipBJ following the proposed nomenclature for R. solanacearum T3Es (11). A ripBJ disruption mutant was generated and used to evaluate the contribution of this effector to pathogenicity on A. thaliana and M. truncatula, and to hypersensitive response (HR) elicitation after infiltration of tobacco leaves.…”
Section: ϫ34mentioning
confidence: 99%
See 2 more Smart Citations
“…Individual R. solanacearum strains typically possess around 60 -75 effectors. Effector repertoire comparison revealed a group of 32 core effectors present in 10 of 11 strains (13). To date, only a few R. solanacearum effectors have been assigned molecular functions and targets (14 -16), but most of these effectors remain functionally uncharacterized.…”
mentioning
confidence: 99%